Answer:
A
Step-by-step explanation:
Answer:
True
Step-by-step explanation:
Answer:
The equation will be "
".
Step-by-step explanation:
Given:
Points (12, 9) = (x, y)
⇒ ![x=9t^2+3](https://tex.z-dn.net/?f=x%3D9t%5E2%2B3)
then,
![\frac{dy}{dt}=18t](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdt%7D%3D18t)
or,
⇒ ![y=6t^3+3](https://tex.z-dn.net/?f=y%3D6t%5E3%2B3)
then,
![\frac{dy}{dt}=18t^2](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdt%7D%3D18t%5E2)
⇒ ![\frac{dy}{dx}=\frac{18t^2}{18t}](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%3D%5Cfrac%7B18t%5E2%7D%7B18t%7D)
![=t](https://tex.z-dn.net/?f=%3Dt)
By using the point slope form.
The equation of tangent will be:
⇒ ![y-9=1(x-12)](https://tex.z-dn.net/?f=y-9%3D1%28x-12%29)
![y-9=x-12](https://tex.z-dn.net/?f=y-9%3Dx-12)
![y=x-12+9](https://tex.z-dn.net/?f=y%3Dx-12%2B9)
![y=x-3](https://tex.z-dn.net/?f=y%3Dx-3)
Order of operations is one way
Answer:
sorry. i have no idea
Step-by-step explanation:
i dont know i tried. sorry.